The PARK2/Parkin receptor on damaged mitochondria revisited—uncovering the role of phosphorylated ubiquitin chains - Matsuda, Noriyuki (Autophagy, 2015)
Phosphorylated ubiquitin produced by PINK1 kinase functions as a PARK2/Parkin activator by derepressing intramolecular autoinhibition of PARK2 E3 activity. Unexpectedly, we revealed that phosphorylated polyubiquitin chain also functions in the PARK2 recruitment process as a PARK2 receptor. Phosphorylated ubiquitin enables us to comprehensively understand how PINK1 and PARK2 catalyzes (phospho-)ubiquitination of depolarized mitochondria and subsequent mitophagy.